Evaluating Behavioral Skills Training as an Evidence-Based Practice When Training Parents to Intervene with Their Children. Issue 6 (November 2021) - Schaefer, John M.; Andzik, Natalie R.
The authors of this systematic review identified 20 individual single-subject studies examining the efficacy of Behavior Skills Training (BST) implemented with parents. Findings indicate that researchers have used BST to successfully train parents to implement a range of evidence-based practices (EBP) with their own children. Parents of children with autism or intellectual disability made up the large majority of participants in these studies. Applying the methodological quality standards set by What Works Clearinghouse (WWC), the authors detail the evidence from 67 individual cases provided by single-subject design research. Practitioners looking to train parents of children with disabilities to implement EBPs can be confident that BST is an effective training practice.